2010
DOI: 10.1016/j.trstmh.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multi-drug resistant tuberculosis in Karachi, Pakistan: identification of at risk groups

Abstract: Multidrug-resistant tuberculosis (MDR-TB) is a possible threat to global tuberculosis control. Despite a disease prevalence of 263/100 000 population Pakistan lacks information on prevalence of drug resistant TB. Our objective was to estimate prevalence of MDR and associated risk factors in patients with pulmonary tuberculosis in Karachi. Six hundred and forty consenting adult patients were enrolled from field clinics from July 2006 to August 2008 through passive case finding. Prevalence of MDR-TB with 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
5
27
2
Order By: Relevance
“…Males were more likely to have MDR-TB than females in some settings [9] whereas the opposite was true in others [8], [13]. Gender was not a risk factor in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Males were more likely to have MDR-TB than females in some settings [9] whereas the opposite was true in others [8], [13]. Gender was not a risk factor in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies identified some risk factors associated with MDR-TB, namely previous TB treatment [8], [9], [10], [11], [12], poor past compliance with treatment [12], [13], HIV infection [9], [14], younger age-group [9], [15], [16], gender [9], [13], foreign born people [9], [16], living in an urban area [15], working in health care [14], type by bacteriology and pulmonary site of TB [14], presence of cavitation in lungs [12], contact with a TB patient [11], smoking or other substance misuse [14], [17], [18], chronic renal failure [19], diabetes [20], use of other anti-microbial medicine [19], being an asylum seeker [14], living in a nursing home [14], being a prisoner [14], and hospitalization history [21]. Inappropriate medical management, absence of directly observed treatment, lack of uniformity between public and private sectors, limited or interrupted drug supply, poor quality and widespread availability of anti-tuberculosis drugs, were also reported as important causes associated with MDR-TB [10], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to World Health Organization (WHO) estimates of 2008, MDR-TB rates range between 1.6 and 22.3% in high-TB-burden countries, including Pakistan (52). Community-based MDR-TB cases are reported to be 4 to 5% of all TB cases in Pakistan (16). Global occurrence of XDR-TB among all MDR-TB cases is reportedly 6.6%, while in Asia, including Bangladesh and Indonesia, it has been reported as 1.5% (43).…”
mentioning
confidence: 99%
“…2,5,6 A higher proportion of pre-and XDR-TB cases (82%) had an unfavourable outcome, similar to the 80% reported elsewhere in South Africa. 7 Unlike studies in Turkey 8 and in Pakistan, 9 where MDR-TB was more common among women, we had similar proportions of male and female DR-TB cases. However, in our study, being * Missing values were not displayed and were found in the following variables: anti-tuberculosis treatment outcome (n = 4, 1.5%), sex (n = 4, 1.5%), baseline smear (n = 29, 10.7%), oral adherence (n = 42, 15.4%), injectable adherence (n = 62, 22.8%), HIV status (n = 7, 2.6%), baseline culture (n = 40, 14.7%), weight (n = 20, 7.4%) and age (n = 33, 12.1%).…”
Section: Discussionmentioning
confidence: 61%